Antiproliferative Effect and Apoptosis Induced in Human Cell Lines by Bruguiera gymnorhiza Barks Methanol Extract - Warsinah, .; Sismindari, .; Susidarti, Ratna Asmah (Indonesian Research Gateway, 2011)
The Antiproliferative effects of methanol extract from Bruguiera gymnorhiza (B. gymnorhiza) barks were tested in vitro against three human cell lines: Hela, Raji and Myeloma cells. The extract was found to have antiproliferative effects against Hela, Raji and Myeloma cells with an IC50 value of 133, 504 and 384 µg/mL, respectively. The antiproliferative test was then performed on Hela, Raji, and Myeloma cells. Cytotoxicity assay of the extract was then determined using MTT method. There were some indications of apoptosis, such DNA fragmentation, as assessed by acrydine orange- ethidium bromide staining. These results indicate that extract from B. gymnorhiza barks can induce apoptosis in human cell lines.Key words: Antiproliferative, Apoptosis, B. gymnorhiza